Regulation of Fibroblast Activation Protein by Transforming Growth Factor Beta-1 in Glioblastoma Microenvironment - Krepela, Evzen; Vanickova, Zdislava; Hrabal, Petr; Zubal, Michal; Chmielova, Barbora; Balaziova, Eva; Vymola, Petr; Matrasova, Ivana; Busek, Petr; Sedo, Aleksi (International journal of molecular sciences, 2021)
The proline-specific serine protease fibroblast activation protein (FAP) can participate in the progression of malignant tumors and represents a potential diagnostic and therapeutic target. Recently, we demonstrated an increased expression of FAP in glioblastomas, particularly those of the mesenchymal subtype. Factors controlling FAP expression in glioblastomas are unknown, but evidence suggests that transforming growth factor beta (TGFbeta) can trigger mesenchymal changes in these tumors. Here, we investigated whether TGFbeta promotes FAP expression in transformed and stromal cells constituting the glioblastoma microenvironment. We found that both FAP and TGFbeta-1 are upregulated in glioblastomas and display a significant positive correlation. We detected TGFbeta-1 immunopositivity broadly in glioblastoma tissues, including tumor parenchyma regions in the immediate vicinity of FAP-immunopositive perivascular stromal cells. Wedemonstrate for the first time that TGFbeta-1 induces expression of FAP in non-stem glioma cells, pericytes, and glioblastoma-derived endothelial and FAP+ mesenchymal cells, but not in glioma stem-like cells. In glioma cells, this effect is mediated by the TGFbeta type I receptor and canonical Smad signaling and involves activation of FAP gene transcription. We further present evidence of FAP regulation by TGFbeta-1 secreted by glioma cells. Our results provide insight into the previously unrecognized regulation of FAP expression by autocrine and paracrine TGFbeta-1 signaling in a broad spectrum of cell types present in the glioblastoma microenvironment.
Keywords: seprase; Fluorescent Antibody Technique; signaling; Cells, Cultured; lidé; Glioblastoma; glioblastoma; Cell Line, Tumor; endopeptidasy; Tumor Microenvironment; fibroblast activation protein; Phosphorylation; regulation of expression; Smad2; kultivované buňky; imunohistochemie; Humans; fosforylace; transforming growth factor beta; Gene Expression Regulation, Neoplastic; fluorescenční protilátková technika; transformující růstový faktor beta1; Transforming Growth Factor beta1; Immunohistochemistry; nádorové mikroprostředí; membránové proteiny; Endopeptidases; Membrane Proteins; tumor microenvironment; glioblastom; nádorové buněčné linie; regulace genové exprese u nádorů